Upaya Meningkatkan Prestasi Belajar Siswa Kelas VII B SMP Negeri 9 Kota Jambi dalam Operasi Hitung Bilangan Bulat Melalui Pemanfaatan Alat Peraga Garis Bilangan - Nurmawati Nurmawati (Universitas Batanghari Jambi, 2019)
An integer counting operation is one of several basic materials in mathematics learning whose applications are used up to college. This shows the importance of understanding counting operations on integers. This study aims to improve student learning achievement in integer counting operation material through the use of number line props. This research is a classroom action research with 3 cycles, in which the research subjects are students of class VII B SMP Negeri 9 Jambi City. The results of the study showed the enthusiasm of students in participating in the learning starting from the first, second and third cycles had increased. In addition, the mastery of learning also increased, namely 23% in the first cycle, 40% in the second cycle and 88% in the third cycle. Other findings in this study are the factors causing student learning difficulties on this subject, among others: (1) Students do not understand adding positive integers with negative integers; (2) Students do not understand subtracting positive integers with negative integers and negative integers with negative integers; (3) Students do not understand dividing positive integers with negative integers and negative integers with negative integers.